Effects of proinsulin misfolding on β‐cell dynamics, differentiation and function in diabetes. (19th September 2018) - Riahi, Yael; Israeli, Tal; Cerasi, Erol; Leibowitz, Gil
Abstract : ER stress due to proinsulin misfolding has an important role in the pathophysiology of rare forms of permanent neonatal diabetes (PNDM) and probably also of common type 1 (T1D) and type 2 diabetes (T2D). Accumulation of misfolded proinsulin in the ER stimulates the unfolded protein response (UPR) that may eventually lead to apoptosis through a process called the terminal UPR. However, the β‐cell ER has an incredible ability to cope with accumulation of misfolded proteins; therefore, it is not clear whether in common forms of diabetes the accumulation of misfolded proinsulin exceeds the point of no return in which terminal UPR is activated. Many studies showed that the UPR is altered in both T1D and T2D; however, the observed changes in the expression of different UPR markers are inconsistent and it is not clear whether they reflect an adaptive response to stress or indeed mediate the β‐cell dysfunction of diabetes. Herein, we critically review the literature on the effects of proinsulin misfolding and ER stress on β‐cell dysfunction and loss in diabetes with emphasis on β‐cell dynamics, and discuss the gaps in understanding the role of proinsulin misfolding in the pathophysiology of diabetes.